Food security in developing countries: Gender and spatial interactions - Romero Hernandez, Catalina; Wichmann, Bruno; Luckert, Martin; Laderach, Peter (Taylor and Francis, 2025)
Food security in developing countries is determined by a variety of economic constraints. Smallholder farmers living near one another face similar socioeconomic conditions but may have different levels of food security. Neighbors can potentially ease economic constraints and promote food security by acting as channels of resources and information. These spatial effects are likely mediated by gender roles and norms. This study estimates gendered spatial effects using a sample of households across seven countries in Africa and Asia.